The Triple Imperative in Fossil Fuel Logistics: Efficiency, Safety, and Environmental Sustainability - Sholihah Eka Permata Sari; Nugroho Adi Sasongko; Purnomo Yoesgiantoro (International Journal of Technology and Education Research, 2026)
Fossil fuels—coal, oil, and natural gas—remain central to global energy despite environmental concerns. This study examines the logistics of transporting these fuels, each with unique challenges. Coal relies on bulk rail and ship transport, raising pollution concerns. Oil uses pipelines and tankers, with risks like spills. Natural gas, especially LNG, requires complex infrastructure for liquefaction, shipping, and regasification. Safety is a major issue due to hazards like explosions and spills, prompting industry reliance on technology and regulations. Environmental impacts include emissions, ecosystem damage, and methane leaks. The paper calls for improved efficiency, safety, and sustainability in logistics. Through case studies, it highlights innovations and best practices to mitigate risks and enhance performance. As the world shifts toward cleaner energy, fossil fuel logistics must evolve to meet environmental standards and societal expectations.